Nanocomposites of various shapes in trihybrid nanofluid flow past a Riga plate with electroosmotic effects - Muhammad Idrees Afridi; Saima Riasat; Saira Iqbal; S. Bilal; A.A. Alderremy; Emad E. Mahmoud (Alexandria Engineering Journal)
Advanced nanocomposites submerged into base fluid to compose ternary hybrid nanofluid have immense thermophysical features for the optimization of thermal processes in renewable energy processes. Ternary hybrid nanofluid underscores their pivotal role in numerous thermal management devices for various interventions such as photovoltaic thermal systems, biomedical appliances, heat engines, tissue engineering etc. The present study utilizes the advanced nanocomposites with various shapes outfitted with electrodes and permanent magnets in the vicinity of electric and magnetic field with electro-osmotic effect. Thermal distribution under the impacts of Lorentz forces is examined graphically for ternary nanofluid with carbon nanotubes as nanoparticle in spherical shape, Al2O3in platelet shape and graphene nano particles in cylindrical shape over the convectively heated Riga plate. Numerical solution is sought to analyze the nonlinear problem by collocation method. Entropy generation analysis is accomplished to enhance the performance of system. Efficiency assessment of advanced nanocomposites in the existence of Lorentz forces is enhanced by carrying out the entropy generation analysis. For the enhancement in modified Hartman number and electroosmotic parameter, the velocity profile is increasing. Increasing Helmholtz-Smoluchowski velocity creates a stronger Coulomb force which encourages more fluid movement. Radiation parameter causes the enhancement in thermal profile. The present examination is the improvement in previous studies by carrying out the analysis with broader range of parameters.